A new concept for a solid-state on-load tap changers - Degeneff, R.C (14th International Conference and Exhibition on Electricity Distribution (CIRED 1997 - Distributing Power for the Millennium), 1997)
This paper presents a new approach for constructing a solid-slate on-load tap changer. Through a judicious choice of the tap changer topology and a novel use of the control, the proposed solid-state on-load tap changer uses fewer thyristors of lower rating than conventional thyristor based tap changer configurations. Further, it is able to accomplish the conventional 16 5/8% laps with fewer physical transformer tap winding leads. The tap changer concept has been experimentally verified at Rensselaer Polytechnic Institute. This paper contains a cost comparison for a 13.8 kV 10 MVA transformer and is presented to illustrate the economic potential of this concept. Depending upon the system voltage, power, and % taps, the approach presented can be 20-60% less expensive than previous efforts to realize solid-state on-load tap changers. (4 pages)